Heterodimers and family-B GPCRs: RAMPs, CGRP and adrenomedullin. (26th October 2004) - Conner, A.C.; Simms, J.; Hay, D.L.; Mahmoud, K.; Howitt, S.G.; Wheatley, M.; Poyner, D.R.
Abstract : RAMPs (receptor activity-modifying proteins) are single-pass transmembrane proteins that associate with certain family-B GPCRs (G-protein-coupled receptors). Specifically for the CT (calcitonin) receptor-like receptor and the CT receptor, this results in profound changes in ligand binding and receptor pharmacology, allowing the generation of six distinct receptors with preferences for CGRP (CT gene-related peptide), adrenomedullin, amylin and CT. There are three RAMPs: RAMP1–RAMP3. The N-terminus appears to be the main determinant of receptor pharmacology, whereas the transmembrane domain contributes to association of the RAMP with the GPCR. The N-terminus of all members of the RAMP family probably contains two disulphide bonds; a potential third disulphide is found in RAMP1 and RAMP3. The N-terminus appears to be in close proximity to the ligand and plays a key role in its binding, either directly or indirectly. BIBN4096BS, a CGRP antagonist, targets RAMP1 and this gives the compound very high selectivity for the human CGRP1 receptor.